Applying Question and Answer Relationship (QAR) Strategy to Enhance Critical Reading Skill of Authentic Text - Jenny Elvinna Manurung; Nidal A.M Jabari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study examined the implementation of the Question and Answer Relationship (QAR) Strategy during the teaching-learning process to enhance the critical reading skill of authentic texts. The study employed classroom action research of fourth-semester students at Tridinanti University. It was implemented for three cycles involving four phases; planning, implementation, observation, and reflection. The data were gathered using three different types of instruments, including interviews, observation, and tests of critical reading. The findings showed that students' critical reading achievement of authentic text increased for each cycle. The question categories of the QAR strategy could help the students in managing difficulties in doing the reading learning activities.